2021
DOI: 10.4315/jfp-20-435
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Cost-Effective Screening for Antimicrobials against Listeria monocytogenes in Ham

Abstract: Ready-to-eat (RTE) meat products, such as deli ham, can support the growth of Listeria monocytogenes (LM) which can cause severe illness in immunocompromised individuals. The objectives of this study were to validate a miniature ham model (MHM) against the ham slice method and screen antimicrobial combinations to control LM on ham using response surface methodology (RSM) as a time- and cost-effective high-throughput screening tool. The effect of nisin (Ni), potassium lactate sodium acetate (PLSDA), lauric argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The lack of fit value was 0.0872 (>0.05), suggesting there is little deviation between the predicted value and the actual value, which belongs to the normal error range, and it is feasible to simulate real 4-factor and 3-level analysis by using this equation. The R 2 value and value of the entire model were 0.9574 and 0.9433, respectively, suggesting that the polynomial model fit the experimental data primely ( Resendiz-Moctezuma et al, 2021 ). Therefore, the best natural preservative ratio for the antibacterial effect of marinated chicken can be selected through this model.…”
Section: Resultsmentioning
confidence: 94%
“…The lack of fit value was 0.0872 (>0.05), suggesting there is little deviation between the predicted value and the actual value, which belongs to the normal error range, and it is feasible to simulate real 4-factor and 3-level analysis by using this equation. The R 2 value and value of the entire model were 0.9574 and 0.9433, respectively, suggesting that the polynomial model fit the experimental data primely ( Resendiz-Moctezuma et al, 2021 ). Therefore, the best natural preservative ratio for the antibacterial effect of marinated chicken can be selected through this model.…”
Section: Resultsmentioning
confidence: 94%
“…Production, storage and distribution of food products require conditions that minimize or terminate development of infections caused, among other things, by bacterial and fungicidal activity [1][2][3][4]. In order to combat pathogenic microorganisms, a wide range of biocidal substances has been suggested that are capable of suppressing their vital activity [5][6][7][8]. Conventional low molecular weight biocides have been applied as bacteriaand-fungi killing agents for years [9][10][11].…”
Section: Introductionmentioning
confidence: 99%